PENGEMBANGAN SUMBER BENIH MINDI (Melia azedarach) UNTUK HUTAN RAKYAT DI JAWA BARAT - Prijanto Pamoengkas; Iskandar Z. Siregar; Nurheni Wijayanto; . Yulianti; Dida Syamsuwida (Jurnal Ilmu Pertanian Indonesia, 2012)
Melia azedarach is mostly found in community forests in West Java. One of the factors that affect forest productivity is high quality seed, but seed quality is not easily obtained by farmers. The general objective research is to provide good quality seeds of Mindi. Specific objectives are: 1) Determine the potential and the distribution of genetic resources of Mindi); 2) Determine the reproductive system; 3) ) improve  seed technology  to develop the seed viability of mindi, and 4) Build the collaborative management of mindi seed source by farmer. Seven  populations of mindi plantation in the community forests were chosen for this research. The study was conducted over three years (2009-2011). Biophysical condition such as  soil, light, temperature, altitude and humidity affect growth, flowering, fertilization and fruit production of mindi. The flowering cycle was proceeded for 6-7 months. The average value of reproductive success (KR) is 58%. The genetic variation of mindi in community forests in West Java was He = 0.1603-0.1956. The thickness of the seed coat, the high  content of lignin and ABA is create a difficulty in seed germination. Prospective populations to be developed for seed sources were proposed namely Sumedang, Wanayasa and Talegong.